A Few Good Trig Identities

Geometry Level 2

1 1 + sin 2 x + 1 1 + cos 2 x + 1 2 + tan 2 x + 1 2 + cot 2 x \dfrac { 1 }{ 1+\sin^{2} {x} } +\dfrac { 1 }{ 1+\cos^{2} {x} } +\dfrac { 1 }{ 2+\tan ^{2} {x} } +\dfrac { 1 }{ 2+\cot ^{ 2 }{ x } }

For all x x on the domain of the tan x \tan x and cot x , \cot x, what is the value of the expression above?

-1/2 1 2 -1 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Yasir Soltani
Jan 25, 2016

= 1 1 + sin 2 x + 1 1 + cos 2 x + cos 2 x 2 cos 2 x + sin 2 x + sin 2 x 2 sin 2 x + cos 2 x = \frac{1}{1+\sin^2 x}+\frac{1}{1+\cos^2 x}+\frac{\cos^2 x}{2\cos^2 x+\sin^2x} +\frac{\sin^2 x}{2\sin^2 x +\cos^2x} = 1 1 + sin 2 x + 1 1 + cos 2 x + cos 2 x 1 + cos 2 x + sin 2 x 1 + sin 2 x = \frac{1}{1+\sin^2 x}+\frac{1}{1+\cos^2 x}+\frac{\cos^2 x}{1+\cos^2 x} +\frac{\sin^2 x}{1+\sin^2 x} = 1 + sin 2 x 1 + sin 2 x + 1 + cos 2 x 1 + cos 2 x = \frac{1+\sin^2 x}{1+\sin^2 x}+\frac{1+\cos^2 x}{1+\cos^2 x} = 1 + 1 =1+1 = 2 =2

Note first that tan 2 x = sec 2 x 1 \tan^{2}x = \sec^{2}x - 1 and that cot 2 x = csc 2 x 1 \cot^{2}x = \csc^{2}x - 1 . The given expression then becomes

1 1 + sin 2 x + 1 1 + cos 2 x + 1 1 + sec 2 x + 1 1 + csc 2 x = \dfrac{1}{1 + \sin^{2}x} + \dfrac{1}{1 + \cos^{2}x} + \dfrac{1}{1 + \sec^{2}x} + \dfrac{1}{1 + \csc^{2}x} =

1 1 + sin 2 x + 1 1 + cos 2 x + cos 2 x cos 2 x + 1 + sin 2 x sin 2 x + 1 = 1 + sin 2 x 1 + sin 2 x + 1 + cos 2 x 1 + cos 2 x = 1 + 1 = 2 \dfrac{1}{1 + \sin^{2}x} + \dfrac{1}{1 + \cos^{2}x} + \dfrac{\cos^{2}x}{\cos^{2}x + 1} + \dfrac{\sin^{2}x}{\sin^{2}x + 1} = \dfrac{1 + \sin^{2}x}{1 + \sin^{2}x} + \dfrac{1 + \cos^{2}x}{1 + \cos^{2}x} = 1 + 1 = \boxed{2} .

Shubham Poddar
Oct 7, 2017

In algebra, if ab = 1 then 1/(a+1) + 1/(b+1) = 1. Apply this one here. You will get the ans.

Stephen Brown
Sep 26, 2017

Note that you can cheat here: since the problem implies that the expression is equal for all defined x, you can simply pick an x and evaluate. For example, at x = π / 4 x=\pi/4 , the expression becomes 2 / 3 + 2 / 3 + 1 / 3 + 1 / 3 = 2 2/3+2/3+1/3+1/3 = 2 . Not in the spirit of the problem, but effective.

Amed Lolo
Jan 27, 2016

Assume a right triangle angle ,& x one of two residuals angles,put near side to angle (a),,&opposite (p)&hypotenuse (h),OK. Sinx=p\h,,,cosx=a\h,,tanx=p\a,,,cotx=a\p. expression=1÷(1+(p^2\h^2))+1÷(1+(a^2\h^2)). +1÷(2+(p^2\a^2))+1÷(2+(a^2\p\^2)). h^2=p^2+a^2. exp=h^2÷(p^2+h^2)+h^2÷(h^2+a^2)+a^2÷(2a^2+p^2)+p^2÷(2p^2+a^2). =h^2÷(2h^2-a^2)+h^2÷(h^2+a^2)+a^2÷(a^2+h^2)+p^2÷(2h^2-a^2).. =(h^2+a^2)÷(h^2+a^2)+(h^2+p^2)÷(2h^2-a^2). =1+(h^2+h^2-a^2)÷(2h^2-a^2)=1+1=2#######

Use LaTex PLEASE

Vitor Santos - 5 years, 4 months ago

Log in to reply

I don't understand what latex, but I want to ask you about my solution .if you mean language text I am sorry it is phone problem OK. Good bye

Amed Lolo - 5 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...